Meningkatkan Jiwa Kewirausahaan Siswa dari Faktor Kompetensi Rasa Ingin Tahu, Berpikir Kreatif, dan Sikap Mengambil Risiko di SMA Lentera Harapan Tangerang [Improving Students' Entrepreneurial Spirit from the Competency Factors of Curiosity, Creative Thinking, and Risk Taking at Lentera Harapan Tangerang High School] - Hutasoit, Rebecca Oktoviana (Magister Teknologi Pendidikan Fakultas Ilmu Pendidikan, Universitas Pelita Harapan, 2022)
The entrepreneurial spirit is now needed. Through the entrepreneurial spirit, the students are expected to become skill and applicable in the daily life. Things that encourage the growth of the entrepreneurial spirit of the students are the curiosity competency, creative thinking and risk-taking attitude. Therefore, this study was conducted to determine whether there is a correlation and influence between the three competences toward the entrepreneurial spirit of the students, and to analyze how significant the influence of them. This study was implemented to 115 students of Lentera Harapan, Tangerang. Collecting data used questionnaire for the competences and entrepreneurial spirit by using SPSS statistical program assistance type 16. To solve the validity types, relationships, and influences is calculated by the formula Pearson and regression, and reliability using Cronbach Alpha. The result of this research showed that there is a correlation and influence between the curiosity competence (0.33), creative thinking (0.19), and risk-taking attitude (0.36) toward the entrepreneurial spirit of students. The three factors are influence toward entrepreneurial spirit as 0.422 and significant to develop the entrepreneurial spirit between the grade X and XI.